An Algorithm for Dynamic Identification of Low-Voltage Topology. Issue 1 (1st February 2023) - Zhou, Cheng; Dai, Shenjian; Pan, Zhicheng; Wu, Hai; Chen, Chen
Abstract: The topology identification of the station area includes two types of household-transformation relationship and branch relationship identification. In this paper, the station area identification signal is sent in phases through the intelligent distribution transformer terminal deployed in the station area, and the branch identification slave installed in each branch line and the terminal identification slave installed in the meter box receive this identification signal to realize the household-transformation relationship and phase identification in the station area. At the same time, the terminal identification slave sends a branch current identification signal, and the branch station identification slave receives the branch identification signal so that the branch relationship can be recognized correctly. Through the identification of household-transformation relationships, phase sequence identification, and branch relationship identification, the correct dynamic topology diagram of the station area can be established.